Physical activity, psychiatric distress, and interest in exercise group participation among individuals seeking methadone maintenance treatment with and without chronic pain. Issue 2 (29th January 2016) - Beitel, Mark; Stults‐Kolehmainen, Matthew; Cutter, Christopher J.; Schottenfeld, Richard S.; Eggert, Kathy; Madden, Lynn M.; Kerns, Robert D.; Liong, Christopher; Ginn, Joel; Barry, Declan T.
Abstract : Background and Objectives: Physical activity may improve chronic pain, anxiety, and depression, which are prevalent among patients in methadone maintenance treatment (MMT), but relatively little is known about the physical activity levels or interest in exercise of patients in MMT. Methods: We used a brief self‐report instrument to assess physical activity levels, chronic pain, psychiatric distress, and interest in exercise group participation among 303 adults seeking MMT. Results: Most (73%) reported no moderate or vigorous intensity physical activity in the past week; 27% met recommended physical activity levels, and 24% reported interest in exercise group participation. Participants with (compared to those without) chronic pain had higher levels of psychiatric distress and were less likely to meet recommended levels of physical activity ( p  < .05), but did not differ significantly in their interest in participating in an exercise group. Participants who met recommended levels of physical activity in the past week were more likely to be men and had lower levels of depression than others ( p  < .05). Conclusions and Scientific Significance: Low levels of physical activity and low interest in exercise group participation among patients entering MMT point to the need for and likely challenges of implementing exercise interventions in MMT. (Am J Addict 2016;25:125–131)